Determination of Antioxidants by Four Different Methods in Medicinally Important Plant Ebenus Stellata of Balochistan - Tareen, Abdul Hakeem; Mandokhail, Aminullah; Samiullah,; Khan, Naqeebullah; -Ur-Rehman Kakar, Attiq; Tariq, Sonia; Kakar, Najeebullah (Al-Nahrain Journal of Science, 2020)
The quantification of a plant, which is vital in medication bearing antioxidant activity of the North West area of the province Balochistan Ebenus Stellata family Fabaceae is explained in this paper. The plant composition was determined chemically through well-known four analytical tests and sensitive EMR operating techniques. The crude extract was obtained from the plant by using methanol, and the antioxidant activity of that extract was measured. Additionally, with the help of spectrophotometer, antioxidant potentials were determined through the DPPH (2, 2-Diphenyl-1-Picrylhydrazyl) assay, Ferric ion (Fe+3) reducing antioxidant power assay, Ferric (Fe+3) reducing antioxidant potential (FRAP) assay, and total antioxidant capacity (TAC) of the phosphomolybdenum assay. The potency of the DPPH assay of Ebenus Stellata was 179 mg/g of ascorbic acid concentration. Moreover, the FRAP and TAC values were 9.2 mg and 35 mg of ascorbic acid/g of Ebenus stellate extract, respectively. Furthermore, RP denotes 2.6 mg/g of ascorbic acid concentration. The concerned plant showed high antioxidant activity.